Perspective on the Production Availability of Animal Protein Source from Livestock in Indonesia - Priyono Priyono; Atien Priyanti (Indonesian Center for Animal Research and Development, 2018)
Human Development Index (HDI) is used to measure overall performance where Indonesia's HDI is ranked 110 out of 187 countries with an index value of 0.684 in 2015. Consumption of animal protein has a relationship with life expectancy and quality of life which determines by the HDI performance. The paper describes on perspective development of animal protein source from livestock in Indonesia. The production development of animal protein source in overall (meat, eggs, and milk) had a positive growth during the period of 1994-2015 with the range of 1-6%/year, except that for buffalo meat production that decreased by 1.77%/year. The animal protein availability of meat was dominated by broiler production, followed by beef, mutton and others. The broiler meat production has the highest growth rate of 6.67%/year. Meanwhile, the animal protein source of non-meat production was dominated by eggs and milk production that its growth rate were 5.98 and 4.29%/year, respectively. In the same period, the meat production share was dominated by poultry meat, the rest derived from large ruminant, small ruminant, and other meat sources. Egg and milk production share also increased significantly during the period and share availability of beef production was less than 25% where its consumer participation was decreased. This indicates that beef is not a primary consumption for the majority people of Indonesia. Development program is needed to encourage an increase of the protein source from poultry meat, large ruminants, small ruminants, and milk.